2022
DOI: 10.1021/acsami.2c16317
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Catalytic Performance through Subsurface Chemistry: The Case of C2H2 Semihydrogenation over Pd Catalysts

Abstract: Subsurface chemistry in heterogeneous catalysis plays an important role in tuning catalytic performance. Aiming to unravel the role of subsurface heteroatoms, C 2 H 2 semihydrogenation on a series of Pd catalysts doped with subsurface heteroatom H, B, C, N, P, or S was fully investigated by density functional theory (DFT) calculations together with microkinetic modeling. The obtained results showed that catalytic performance toward C 2 H 2 semihydrogenation was affected significantly by the type and coverage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…In another study, involving the hydrogenation of 1,3-butadiene on Pd (110)-oriented surfaces, it was observed that the presence of both weakly π-bonded 1,3-butadiene and subsurface hydrogen atoms is required to achieve catalytic activity [ 12 ]. Furthermore, Wu et al [ 13 ] also attributes enhancements in catalytic performance to subsurface chemistry. In this cited work, focused on the partial hydrogenation of acetylene over Pd catalysts, the authors claim that the main reason for the catalytic performance of the active site can be tuned based on the distinctive electronic and geometric structures of Pd derived as a result of the presence of the corresponding subsurface heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, involving the hydrogenation of 1,3-butadiene on Pd (110)-oriented surfaces, it was observed that the presence of both weakly π-bonded 1,3-butadiene and subsurface hydrogen atoms is required to achieve catalytic activity [ 12 ]. Furthermore, Wu et al [ 13 ] also attributes enhancements in catalytic performance to subsurface chemistry. In this cited work, focused on the partial hydrogenation of acetylene over Pd catalysts, the authors claim that the main reason for the catalytic performance of the active site can be tuned based on the distinctive electronic and geometric structures of Pd derived as a result of the presence of the corresponding subsurface heteroatoms.…”
Section: Introductionmentioning
confidence: 99%